Ferroptosis in early brain injury after subarachnoid hemorrhage: review of literature - Junlin Kang; Shilai Tian; Lei Zhang; Gang Yang (Chinese Neurosurgical Journal, 2024)
Abstract Spontaneous subarachnoid hemorrhage (SAH), mainly caused by ruptured intracranial aneurysms, is a serious acute cerebrovascular disease. Early brain injury (EBI) is all brain injury occurring within 72 h after SAH, mainly including increased intracranial pressure, decreased cerebral blood flow, disruption of the blood-brain barrier, brain edema, oxidative stress, and neuroinflammation. It activates cell death pathways, leading to neuronal and glial cell death, and is significantly associated with poor prognosis. Ferroptosis is characterized by iron-dependent accumulation of lipid peroxides and is involved in the process of neuron and glial cell death in early brain injury. This paper reviews the research progress of ferroptosis in early brain injury after subarachnoid hemorrhage and provides new ideas for future research.